Zanamivir for the treatment of avian influenza infections in humans. Issue 1 (January 2010) - Reece, Phillip Andrew
Zanamivir is currently not recommended by the WHO for the first-line treatment of human influenza A (H5N1) infections. Zanamivir pharmacokinetics and antiviral efficacy were reviewed to assess the basis for this recommendation. Following inhalation of 10 mg zanamivir in healthy humans, the drug is widely distributed throughout the lungs. Mean lung sputum concentrations of zanamivir are 1441 and 235 ng/ml at 6 and 12 h postinhalation, respectively. Following repeated dosing to patients, mean steady-state Cmax and Cmin plasma zanamivir concentrations are approximately 60 and 4 ng/ml, respectively. Zanamivir has high in vitro activity against H5N1 strains isolated from patients (IC50 0.3–0.7 ng/ml) including oseltamivir-resistant strains. These data support a reassessment of zanamivir's role in the treatment of human H5N1 infections